2011
DOI: 10.1186/1471-2407-11-207
|View full text |Cite
|
Sign up to set email alerts
|

Antiprogestin mifepristone inhibits the growth of cancer cells of reproductive and non-reproductive origin regardless of progesterone receptor expression

Abstract: BackgroundMifepristone (MF) has been largely used in reproductive medicine due to its capacity to modulate the progesterone receptor (PR). The study of MF has been expanded to the field of oncology; yet it remains unclear whether the expression of PR is required for MF to act as an anti-cancer agent. Our laboratory has shown that MF is a potent inhibitor of ovarian cancer cell growth. In this study we questioned whether the growth inhibitory properties of MF observed in ovarian cancer cells would translate to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
111
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(120 citation statements)
references
References 63 publications
6
111
2
1
Order By: Relevance
“…But the proliferative effect was significantly decreased (P < 0.05) and cell death was observed at high concentrations of P4 (5,10,20,40 and 80 μmol/L) at both 3 and 6 d. The addition of RU486 blocked the proliferative effect of low P4 concentrations but failed to block the cytotoxic effect of P4 at high concentrations. RU486 alone showed a P4 mimetic effect at high concentrations but, when P4 and RU486 were combined, a marked enhancement of the toxic effect was observed.…”
Section: Repeated Exposure Of P4 and Ru486 In Sk-n-as Cellsmentioning
confidence: 95%
See 2 more Smart Citations
“…But the proliferative effect was significantly decreased (P < 0.05) and cell death was observed at high concentrations of P4 (5,10,20,40 and 80 μmol/L) at both 3 and 6 d. The addition of RU486 blocked the proliferative effect of low P4 concentrations but failed to block the cytotoxic effect of P4 at high concentrations. RU486 alone showed a P4 mimetic effect at high concentrations but, when P4 and RU486 were combined, a marked enhancement of the toxic effect was observed.…”
Section: Repeated Exposure Of P4 and Ru486 In Sk-n-as Cellsmentioning
confidence: 95%
“…A single 48-h exposure to P4 at a range of concentrations (0.1, 1, 5, 10, 20, 40 and 80 μmol/L) caused significant (P < 0.05) cell death at higher concentrations (20,40 and 80 μmol/L) in PC-12 cells, but no toxicity was observed at lower concentrations (0.1, 1, 5 and 10 μmol/L) (Figure 1A). SK-N-AS cells exposed to P4 produced a U-shaped response curve for viability.…”
Section: Single Exposure To P4 In Pc-12 and Sk-n-as Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the anti-proliferative effects observed in vitro and in vivo for PRAs (Freeburg et al, 2009b;Goyeneche et al, 2007;Ohara et al, 2007;Poole et al, 2006;Tieszen et al, 2011), the broader utility of this class in treating other benign and malignant growth conditions has not gone unnoticed Robertson et al, 1999;Rocereto et al, 2000;Wilkens et al, 2008). In the closely related condition of uterine fibroids, small studies have demonstrated a reduction in myoma volume and uterine bleeding with asoprisnil and RU-486 (Chabbert-Buffet et al, 2005;DeManno et al, 2003;Fiscella et al, 2006).…”
Section: Clinical Evaluation In Healthy Women and Women With Endometrmentioning
confidence: 99%
“…Ablation of PR-B promoted cellular proliferation, by approximately 20% compared with control, supporting the notion that PR-B acts as a break on progesterone function. It is noteworthy that breast and endometrial malignancy is often accompanied by disruption of PR-A and PR-B expression or altered functional PR responses (Arnett-Mansfield et al, 2004;De Vivo et al, 2002;Kobayashi et al, 2010;McGowan et al, 2004), an observation which has triggered interest in the potential utility of PRAs for oncology (Fuhrmann et al, 2000;Poole et al, 2006;Tieszen et al, 2011;Wiehle et al, 2011). Recent evidence has also confirmed the existence of a functional third isoform, PR-C which lacks AF-2 and AF-3 domains and appears to act as a sink for progesterone and have a function in regulating the onset of parturition (Condon et al, 2006).…”
Section: Progesterone Receptor Structure and Functionmentioning
confidence: 99%